HUBUNGAN BEBAN KERJA DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP RSU ADVENT MEDAN - Eva Kartika Hasibuan; Adventy Riang Bevy Gulo; Masri Saragih; Putri Liana (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Workload is a condition that burdens the workforce, both physically and non-physically in completing work. Excessive workload can cause a person to become nervous which leads to stress. Workload must be considered because workload can affect nurse performance and indirectly affect nursing services to patients. The purpose of this study was to find out whether there is a relationship between workload and nurse performance room at Advent Hospital. This type of research is quantitative research with a non-experimental design with a cross-sectional method. The object of this study were 34 nurses and the sampling technique used was total sampling where the entire population will be sampled. A questionnaire was used in collecting data and analyzed by using the Chi Square correlation test. The results show that the majority of nurses has a moderate workload of 25 respondents (73.5%) and the majority of nurses has good performance of 28 respondents (82.4%). The statistical results show that there is a significant relationship between workload and the performance of nurses in the inpatient ward of Advent Hospital, with a significance level of p value 0.02 (<0.05). So it can be concluded that the lighter the workload the better the nurse's performance. It is expected that the hospital will evaluate the workload and efforts of nurses to improve performance so as to improve the quality of service in providing nursing care services.